METHODS OF ORGANIZING LABORATORY TRAINING IN THE COURCE FOR MECHANICS USING MODERN INFORMATION TECHNOLOGIES - Hamdamov Begali Isroilovich (Web of Journals Publishing, 2025)
In our paper we examine the problem of increasing the effectiveness of training specialists in educational institutions. It is shown that the professional readiness of students as a personal quality and an essential prerequisite for the effective activity of a specialist, the successful performance of their duties, the correct use of knowledge and experience, helps to quickly adapt to working conditions and promotes further professional development.
Keywords: Laboratory classes, development of educational and professional practical skills, form of educational classes.